TYPES AND CHARACTERISTICS OF GUEST ACCOMMODATION FACILITIES (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2026)
This article examines the theoretical foundations of the development of hotels and family guest houses, their role in tourism infrastructure, and their economic significance. The study analyzes the advantages and disadvantages of hotel enterprises and family guest houses, service quality, management efficiency, and foreign experience. In addition, the importance of digital technologies, marketing strategies, and regional tourism opportunities in the development of the hospitality industry is substantiated. Based on the research findings, scientific and practical recommendations for the development of hotels and family guest houses were developed.